Frontal-temporal disconnection abolishes object discrimination learning set in macaque monkeys. - Browning, P; Easton, A; Gaffan, D (2007)
Two previous studies have shown that frontal-temporal disconnection in monkeys, produced by unilateral ablation of frontal cortex in one hemisphere and of visual inferior temporal cortex in the opposite hemisphere is entirely without effect on visual object-reward association learning in concurrent discrimination tasks. This is a surprising finding in light of the severe impairments that follow frontal-temporal disconnection in many other tests of visual learning and memory, including delayed matching-to-sample and several conditional learning tasks. To explore the limits of this preserved object-reward association learning, we trained monkeys on visual object discrimination learning set (DLS) prior to frontal-temporal disconnection. As a result of training with single object-reward associations, the monkeys acquired a proficient learning set, evidenced by the rapid learning of new single object-reward association problems. This rapid learning was not affected by unilateral ablations of either inferior temporal cortex alone or frontal cortex alone but was severely impaired after final surgery to complete the disconnection. Moreover, each individual monkey now learned single object-reward association problems at the slow rate at which that individual had learned such problems before the formation of learning set. This result shows that frontal-temporal disconnection abolishes visual learning set.